Generation and Characterization of Bio-Oil Obtained From The Slow Pyrolysis of Oil Palm Empty Fruit Bunches at Various Temperatures - Siti Jamilatun; Dhias Cahya Hakika; Dwita Sarah; Anggun Puspitasari (Elkawnie, 2024)
Abstract: In the last decade, biomass pyrolysis has received more attention in the renewable energy sector. This technology converts biomass to obtain valuable products: bio-oil, biochar, and gas. Bio-oil is a liquid product from pyrolysis that can be used to fuel boilers and furnaces, or further processed to produce fuel oil and chemical products. In this study, bio-oil was generated from slow pyrolysis of oil palm empty fruit bunches (OPEFB) at various temperatures. The objective of this research is to investigate the effect of temperature on the properties of products generated from the pyrolysis of OPEFB. Six different pyrolysis temperatures ranging from 300 to 700℃ were used to produce bio-oil. It was found that operating temperature affected the product yield and its properties significantly. The higher the operating temperature of slow pyrolysis, the amount of bio-oil produced was also increased with a decrease in biochar yield. The highest yield of bio-oil was found to be 55.53% at a pyrolysis temperature of 700℃ with a yield of biochar and syngas was 24.22% and 20.25%, respectively. The GC-MS analysis was used as a quantitative means to characterize the liquid pyrolysis product. The findings of GC-MS showed that bio-oil generated in this study was dominated by phenols and ketones. In conclusion, pyrolysis of OPEFB demonstrates significant potential for industrial applications to generate valuable products especially bio-oil, providing a renewable alternative to fossil fuels.Abstrak: Dalam satu dekade terakhir, pirolisis biomassa semakin mendapat perhatian di sektor energi terbarukan. Teknologi ini mengubah biomassa menjadi produk-produk yang bernilai seperti: bio-oil, biochar, dan gas. Bio-oil adalah produk cair dari pirolisis yang dapat digunakan sebagai bahan bakar boiler dan furnace, atau diproses lebih lanjut untuk menghasilkan bahan bakar minyak dan produk kimia. Dalam penelitian ini, bio-oil dihasilkan dari proses pirolisis lambat tandan kosong kelapa sawit (TKKS) pada berbagai kondisi suhu. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh suhu terhadap karakteristik produk yang dihasilkan dari pirolisis TKKS. Berbagai variasi suhu pirolisis dari rentang 300 hingga 700℃ digunakan untuk menghasilkan bio-oil. Hasil penelitian menunjukkan bahwa suhu pirolisis mempengaruhi yield produk dan karakteristiknya secara signifikan. Semakin tinggi suhu operasi pirolisis, jumlah bio-oil yang dihasilkan juga semakin meningkat, namun diikuti dengan penurunan yield biochar. Yield tertinggi bio-oil yaitu sebesar 55,53% diperoleh pada suhu 700℃ diikuti dengan yield biochar dan syngas masing-masing sebesar 24,22% and 20,25%. Analisis GC-MS digunakan sebagai metode kuantitatif untuk mengkarakterisasi produk cair dari pirolisis. Hasil GC-MS menunjukkan bahwa komposisi bio-oil yang dihasilkan dalam penelitian ini didominasi oleh senyawa fenol dan keton. Penelitian ini menjanjikan potensi dari pirolisis TKKS untuk aplikasi industri guna menghasilkan produk bernilai tinggi berupa bio-oil sebagai penyedia sumber energi terbarukan pengganti bahan bakar fosil.